2017
DOI: 10.4236/ojms.2017.74035
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment Due to Heavy Metals Exposure via Consumption of Bivalves Harvested from Marudu Bay, Malaysia

Abstract: Concern over health risk from consumption of bivalves originating from Marudu Bay is escalating due to the rapid agricultural development surrounding the bay. This has motivated us to estimate the health risk index (HRI) of heavy metals from four commercially important and highly exploited bivalve species which are abundant in the bay. Samples (n = 30) of green mussel (Perna viridis), Asiatic hard clam (Meretrix meretrix), Pacific oyster (Crassosstrea gigas) and marsh clam (Polymesoda expansa) were acquired fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…The HI value (0.56) of the present study was <1 depicting low risk of exposure for consumers of periwinkles. The HI value of the present study is less than that [37] for four different clams but agrees with that (0.45) in fish reported in the Niger Delta region [38]. The percentage make-up of the HI was in the order Pb > Cr > Cd> > Zn > Ni > Cu indicating the elevated input of Pb, Cr and Cd concentrations in the periwinkles examined.…”
Section: Target Hazard Quotientsupporting
confidence: 82%
“…The HI value (0.56) of the present study was <1 depicting low risk of exposure for consumers of periwinkles. The HI value of the present study is less than that [37] for four different clams but agrees with that (0.45) in fish reported in the Niger Delta region [38]. The percentage make-up of the HI was in the order Pb > Cr > Cd> > Zn > Ni > Cu indicating the elevated input of Pb, Cr and Cd concentrations in the periwinkles examined.…”
Section: Target Hazard Quotientsupporting
confidence: 82%
“…Se ha reportado que el mercurio puede ocasionar alteración en células sanguíneas de moluscos bivalvos pudiendo a ciertas concentraciones tener efecto letal en organismos acuáticos (Jakimska et al, 2011;Denil et al, 2017). Otros investigadores deducen la presencia de mecanismos de defensa frente a los metales a través de vesículas que facilitan la excreción celular (Dallinger, 1993;Claisse et al, 2001), o mediante una protección a través de sus valvas como biopelículas de protección (Scardino et al, 2013).…”
Section: Discussionunclassified
“…It has been reported that mercury can cause a cellular alteration in blood cells of bivalve molluscs, and an absolute concentration can have a lethal effect in aquatic organisms (Jakimska et al, 2011;Denil et al, 2017). Other researchers deduce the presence of protection mechanisms against metals through vesicles that facilitate cell excretion (Dallinger, 1993;Claisse et al, 2001), or defense throughout their shells as protective biofilms (Scardino et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…where MPI is the metal pollution index, and MCi is the concentration of metal i in the soft tissues of oysters (Denil et al 2017). The criterion for evaluating heavy metal pollution status according to MPI was summarized in Table 1 ( Jamil et al 2014).…”
Section: Metal Pollution Assessmentmentioning
confidence: 99%